Macluraparishin C Enhances Neuroprotection Against Oxidative Stress-Induced Neurodegeneration by Activating the Antioxidant/MAPK Signaling Pathway - Md Shiblee Sadik Sabuj; Md Sadikul Islam; Md Rashedunnabi Akanda; Joonseok Lee; Ryunhee Kim; Seung Hyun Lee; Ye Ji Kim; Jin Min Oh; Hyeon Gyeong Ro; In-Shik Kim; Dongchoon Ahn; Sang-Youel Park; et al. (Molecular Neurobiology, 2025)

ELF18-INDUCED LONG NONCODING RNA 25 positively regulates the pathogen defense-related CYP82C2 expression in Arabidopsis - Jun Sung Seo; Moon-Joo Lee; Jimin Lee; Nuri Oh; So-Young Jang; Ye In Cho; Jin-Ho Kang; Jang-Kyun Seo; Hye Sun Cho; Moonhyuk Kwon; Choonkyun Jung (Journal of Plant Biology, 2025)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of gene expression during plant immune responses. In this study, we identified a novel lncRNA, ELF18-INDUCED LONG NONCODING RNA 25 ( ELENA25 ), located in the intergenic region between AT4G31960 and CYTOCHROME P450, family 82, subfamily C, polypeptide 2 ( CYP82C2 ) in Arabidopsis. ELENA25 was initially identified through custom lncRNA microarray data. Here, its full-length sequence (810 bp) was determined using primer walking and confirmed by sequencing. ELENA25 expression was preferentially induced by flg22, a bacterial pathogen-associated molecular pattern (PAMP), in a late-phase and FLS2 receptor-dependent manner. Neighboring genes AT4G31960 and CYP82C2 were also flg22-inducible, with expression abolished in the fls2 mutant background. To assess whether ELENA25 regulates the expression of nearby genes, we generated ELENA25 -overexpressing (OX) and knockout (KO) plants. In ELENA25 OX lines, CYP82C2 expression was significantly upregulated under normal and flg22-treated conditions, while AT4G31960 expression remained unchanged. Conversely, in the elena25 mutants (KO), CYP82C2 expression was significantly reduced, indicating that ELENA25 positively regulates CYP82C2 transcription. Expression levels of other nearby cytochrome P450 genes, including CYP82C3 and CYP82C4 , and other indole glucosinolate-related CYP genes were not affected by ELENA25 expression changes. Collectively, our results demonstrate that ELENA25 is a flg22-inducible lncRNA that specifically enhances CYP82C2 expression in a FLS2-dependent manner. This study provides new insights into the role of lncRNAs in plant innate immunity, highlighting ELENA25 as a positive regulator of defense-related gene expression.

Helical donor–acceptor bulk heterojunctions for dissymmetric circularly polarized light detection - Inho Song; Jaeyong Ahn; Sang Hyuk Lee; Sangwook Lee; Seoyoung Kim; Ye In Cho; Joon Hak Oh (Chemical Engineering Journal, 2025)

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)